Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Volume II (Tables) Government of Rajasthan - Planning Commission (Planning Commission, 1990)
Outlay and expenditure during the seventh plan physical target and achievement during the seventh plan Draft eighth five year plan (1990-95) and annual (1991-92)outlay by head of development Centrally sponsored schemes- outlay and expenditure Proposals for programme/project, Statement regarding externally aided projects Rural component of draft eighth five year plan (190-95) annual plan (1991-92).
Government of Rajasthan, Planning Department